In vitro assessment of bioactivities of marine-derived fungi isolated from Manila Bay, Luzon, Philippines - Argosino, Danielle Louise S. (Animo Repository, 2024)
Marine fungi are microscopic organisms known to produce various secondary metabolites that have significantly contributed to the research of natural products. Several bioactive compounds from different environmental sources are presently utilized for developing drugs against bacterial and fungal infections. The study aimed to isolate and identify marine-derived fungi from Manila Bay. Secondary metabolites were extracted in vacuo from these fungi to determine the bioactivities against Candida albicans ATCC 10231 and Candida krusei. Results showed that there were 11 different marine-derived fungi isolated and identified up to the genus level. Using available taxonomic key, some of the following marine fungi genera identified were: (i) Cladophialophora, (ii) Penicillium, (iii) Aspergillus, (iv) Chrysosporium, (v) Trichoderma, and (vi) Cladosporium. Based on disk diffusion assays, all crude extracts showed no inhibitory activities against C. albicans ATCC 10231 and C. krusei. This study provides a baseline knowledge on the obtained secondary metabolites from marine-derived fungal isolates and their potential in creating new experimental frameworks for further research on their possible inhibitory activities against a wider range of test organisms.